USE OF TECHNIQUE OF REPERTUARY GRILLES IN THE FORMATION OF INTERPERSONAL RELATIONSHIPS OF JUNIOR SCHOOLCHILDREN - Z.M. Miroshnyk; O.Yu. Mykhaylenko (Academy of Cognitive and Natural Sciences, 2022)
This article is an attempt to build individual space for younger pupils using the technology of repertory grids.